Integration of Kepasundan Values Into Historical Heritage: An Analysis of The West Java People’s Struggle Monument (MONJU) From A Macroeconomic Perspective - Danu Anugrah Saputra; Khabib Fathurahman; Mentari Ramadani; Fauzie Hakim Mulyady; Witri Saren Simanjorang; Muhammad Raihan Firdaus; Muhamad Azka Nursyifa (Journal of Literary and Linguistic Research, 2026)
This study examines the integration of Kepasundan values into the historical heritage of the Monument of the Struggle of the West Java People and evaluates its implications for regional macroeconomic development. Employing an empirical qualitative case study design supported by secondary socioeconomic data from 2015 to 2023, the research analyzes historical documents, tourism statistics, economic reports, and cultural heritage records through thematic and interpretive content analysis. The findings reveal that Kepasundan values are embedded within the monument through historical narratives, collective memory construction, and cultural representation that strengthen local identity and heritage significance. The study further demonstrates that the cultural value of MONJU has been transformed into economic value through heritage tourism development, creative economic activities, and cultural consumption practices. Evidence indicates continuous growth in tourist visits, creative business formation, and tourism related revenue associated with the monument. At the macroeconomic level, heritage preservation contributes to regional income generation, employment expansion, and creative economy growth while supporting inclusive development objectives. The study concludes that Kepasundan based heritage preservation functions as both a cultural asset and a strategic development resource that promotes sustainable regional development in West Java.